Smart EOQ Models: Incorporating AI and Machine Learning for Inventory Optimization (Global Journal of Science Frontier Research, 2025)
The framework reduced total costs by 24.9% versus stochastic EOQ benchmarks. Key innovation: closed-loop control where ₜ = RL(ₜ) adapts to real-time supply-chain states.
Keywords: dynami c EOQ; reinforcement learning; stochastic inventory control; perishable inventory